Flexible Gas Sensors: Room‐Temperature Solid‐State Grown WO3−δ Film on Plastic Substrate for Extremely Sensitive Flexible NO2 Gas Sensors (Adv. Mater. Interfaces 1/2018). Issue 1 (10th January 2018) - Annapureddy, Venkateswarlu; Kim, Yonghun; Hwang, Geon‐Tae; Jang, Ho Won; Kim, Sung‐Dae; Choi, Jong‐Jin; Cho, Byungjin; Ryu, Jungho
Abstract : A simple, scalable, and time‐ and cost efficient approach for enhancement of sensing capability of chemiresistive flexible gas sensors based on nonstoichiometric tungsten oxide (WO3−δ ) created using the granule spray in vacuum technique at room temperature is demonstrated. A linear sensor response was achieved for gas concentrations of sub‐ppm to tens of ppm with the detection limit 1.88 (±0.128) for NO2 gas. The gas detection response/recovery (17/25 s) time is relatively fast. More details can be found in article number 1700811 by Byungjin Cho, Jungho Ryu and co‐workers.